DISRUPTIVE TECHNOLOGIES FOR SUSTAINABLE DEVELOPMENT proceedings of the International Conference on Application of AI, ML, DL, Big Data on Recent Societal Issues (CARSI 2023). - Nagappan, G.; Uma Rani, V. (CRC PRESS, 2024)
We feel greatly honoured to have been assigned the job of organizing the AICTE Sponsored International Conference on Application of AI, ML, DL, Big Data on Recent Societal Issues (ICARSI'2023) on April 21 & April 22,2023 at Saveetha Engineering College. The international conference is a platform that brings together the brightest minds from across the globe to share their ideas and insights on the recent societal issues with Artificial intelligence, Machine Learning, Deep Learning, Big data and emerging technologies. With an aim to promote collaboration and foster innovation, this conference promises to be a melting pot of ideas and knowledge sharing.
Keywords: Disruptive technologies -- Congresses.; Sustainable development -- Congresses.